Science Learning Using Canva-Based Student Worksheets in Elementary Schools - Rohmah Khasanah; Lina Putriyanti; Joko Siswanto (LPPM Undiksha, 2025)
Science learning in elementary schools continues to face challenges, particularly low student engagement and suboptimal learning outcomes. This condition is influenced by the dominance of conventional, teacher-centered instructional approaches that have not yet facilitated meaningful and interactive learning activities. This study aimed to analyze the effectiveness of Canva-based worksheets in improving elementary school students’ science learning outcomes. This research employed a quasi-experimental method with a Nonequivalent Control Group Design. The research subjects consisted of 52 fifth-grade elementary school students divided into an experimental group and a control group. Data were collected through tests and observations, with research instruments including a validated science learning achievement test in the form of pretests and posttests, as well as observation sheets to record students’ learning activities during the instructional process. Data analysis was conducted using prerequisite tests, including normality and homogeneity tests, followed by hypothesis testing using an Independent Samples t-test and analysis of learning improvement using N-Gain scores. The results indicated a significant difference in learning outcomes between the experimental and control groups, with the experimental group demonstrating a higher improvement in science learning outcomes than the control group. The findings conclude that Canva-based worksheets are effective in improving elementary school students’ science learning outcomes. The implications of this study suggest that the use of interactive digital media such as Canva can serve as an alternative instructional strategy to enhance student engagement and deepen conceptual understanding in science learning.